MODEL BELIEF-ADJUSMENT DAN PERSEPSI INVESTOR: EKSPERIMENTASI RANGKAIAN INFORMASI PENDEK SEDERHANA DAN RESPONS SIMULTAN - SUARTANA, I WAYAN; SUHENDRO, SARING (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 2 (2007), 2007)
The previous research found that there was effect of positive and negativeinformation order of company annual reports. The objective of this research is to examinewhether the order of positive and negative information of a company in the president letterin annual reports can influence the perception of the investor about the company. Thesubjects of this research are the students of Magister of Management Program in one ofState University in Indonesia. The method used is laboratory experiment. The result of thisresearch implies that the ordering of positive and negative information of a company inimpression management of annual reports can influence investor's perception. Positiveinformation presented at the first part will result in positive judgment on the previous andpotential performance compare with receiving negative information on the first part.
Keywords: positive and negative information, belief adjustment model, primary effect, impression management